If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 9) = 30 Reorder the terms: 3(9 + x) = 30 (9 * 3 + x * 3) = 30 (27 + 3x) = 30 Solving 27 + 3x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3x = 30 + -27 Combine like terms: 27 + -27 = 0 0 + 3x = 30 + -27 3x = 30 + -27 Combine like terms: 30 + -27 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 2(x-22)+4(x-4)=48 | | C=8.5x+6y | | 4(x-3)+19=3(x+5) | | 4(x+8)=28 | | 9x+5-27x=7-8x-15 | | 12x-(6x-2)=38 | | 18=8+10(x-11) | | 7x-2(x-3y)-4y= | | X=2.5X+10 | | 9x+1.4=4x+0.9 | | 5x+1.5=2x+0.6 | | 4x+1.5=x | | 3x-0.1=2x | | 3x-0.4=2x | | 6-9w=4 | | 3x-0.6=x | | 4x-0.4=3.4 | | 1X+36=3X-12 | | 2(13-x)+4x=46 | | 1.7x-1.7+x-3.1= | | -5+36w=97 | | 120-2x=43+15 | | 21t+17=80 | | 12-8x=144-36x | | 3(5x+9)=-26+8 | | 6y-14=34 | | 6+3+4mn= | | 3x+25=12x+65 | | 35x+25=12x+65 | | -6b-8=10 | | 2+11(m-6)= | | 5x+3+2x=17 |